Pengaruh Profitabilitas, Likuiditas, Leverage, dan Capital Intensity terhadap Agresivitas Pajak pada Perusahaan Pertambangan yang Terdaftar di BEI Periode Tahun 2015-2019 - Manalu, Sintya Erika Reza; Lawita, Florencia Irena (UNIVERSITAS KALBIS, 2025)
This study aims to determine the effect of profitability, liquidity, leverage and capital intensity on tax agressiveness in mining compannies listed on the IDX for the 2015-2019 period. This study uses quantitative research methods using secondary data. The population in this study uses mining companies listed on the IDX. The sample in this study totaled 20 companies with the 2015-2019 period. Data analysis in this study used multiple regression analysis. The results showed that profitability has a negative effect on tax aggressiveness, liquidity has a negative effect on tax agressivenness, leverage has a negative effect on tax agressivenness, capital intensity has no effect on tax agrressiveness,